Pernafasan Active Cycle of Breathing Meningkatkan Aliran Ekspirasi Maksimum Penderita Tuberkulosis Paru - Tintin Sukartini; Sriyono Sriyono; Iwan Widia Sasmita (Jurnal Ners, 2007)
Introduction: Tuberculosis bacterial can cause fibrosis tissue in lung. Fibrosis decrease elasticity and compliance of lung as a result, there will be air ventilation and oxygenation disorder, thus it will decrease peak expiratory flow rate (PEFR). The objective of this study was to analyze the effect of active cycle of breathing technique on raised peak expiratory flow rate (PEFR). Method: A quasy experimental purposive sampling design was used in this study. There were 14 sample who met in inclusion criteria divided into 7 subjects for intervention group and 7 subject for control group. Data were analyzed by using Paired t-Test, Independent t-Test, Wilcoxon Signed Rank Test, and Mann Whitney U Test with significance level α≤0.05. Result: The result showed that active cycle of breathing had significance level on increased peak expiratory flow rate (PEFR) (p=0.001). Discussion: It can be concluded that active cycle of breathing has effect on raise peak expiratory flow rate. Further study are recommended to measure the effect of active cycle of breathing on raised maximum midexpiratory flow rate (MMFR50-75%).